AESTHETIC AND ETHICAL EDUCATION OF STUDENTS IN FINE ARTS LESSONS (Academicia Globe: Inderscience Research, 2023)
The article describes the role of fine arts and the teacher in the aesthetic and moral education of students, the types of visual arts taught in school according to their purpose and content. ideas are given that visual art develops spiritual outlook, ideological belief, thinking ability, visual memory, creative imagination, artistic taste, and aesthetic feeling in students.